1996
DOI: 10.1099/0022-1317-77-5-977
|View full text |Cite
|
Sign up to set email alerts
|

Immune cell infiltration in corneas of mice with recurrent herpes simplex virus disease

Abstract: Reactivation of latent herpes simplex virus type 1 (HSV-1) infection was induced by UV irradiation of the corneas of latently infected mice. On days 1--4 after stimulation, infectious virus was sought in nervous and ocular tissue. On days 4, 7 and 10, eyes with either recurrent epithelial or stromal disease and appropriate controls were stained to identify immune cells and HSV-1 antigens. The maximum incidence of infectious virus was on day 2 when 5/10 ophthalmic parts of the trigeminal ganglion yielded HSV. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 20 publications
1
35
0
Order By: Relevance
“…In this case, however, the virus being transported is likely to be enveloped. Nevertheless, the chances of Schwann cells becoming infected may be low since only small amounts of virus appear to be produced as a result of reactivation (37) and the axon involved may be myelinated.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, however, the virus being transported is likely to be enveloped. Nevertheless, the chances of Schwann cells becoming infected may be low since only small amounts of virus appear to be produced as a result of reactivation (37) and the axon involved may be myelinated.…”
Section: Discussionmentioning
confidence: 99%
“…These cellular interactions are assumed to result in the induction and perpetuation of a chronic inflammatory process resulting in corneal damage (2,3,7,8) activation of resident cells can be heavily modulated by the Th1-derived cytokine IL-17 (21)(22)(23)(24)(27)(28)(29)(30). Accordingly, the potential interactive role of IL-17 and corneal fibroblasts in the induction and perpetuation of inflammatory processes in human HSK was hypothesized.…”
Section: Discussionmentioning
confidence: 99%
“…In the preclinical phase, when HSV-1 replicates in the corneal epithelium, neutrophils invade the underlying corneal stroma (3). This transient response, triggered by replicating virus (4,5), is thought to control HSV replication and limit viral spread into peripheral tissues (6,7). During the second phase, i.e., the clinical phase, a second wave of inflammatory cells, predominantly consisting of neutrophils, infiltrates the corneal stroma (8).…”
Section: Il-17 Expression In Human Herpeticmentioning
confidence: 99%
“…؉ T cells play a major role in HSV-1-mediated corneal pathogenesis (1,25,26,49). Furthermore, we have previously shown that the CS exacerbation in gK-immunized mice correlates with CD8 ؉ T cells, but not with CD4 ؉ T cells or macrophages (44).…”
Section: Discussionmentioning
confidence: 99%